Impact of Role Conflict on Marital Quality of Dual Career Couples in Peshawar, Pakistan - Khalil ur Rahman; Rashid Khan (The Journal of Humanities & Social Sciences, 2021)
This paper attempts to explore the impact of role conflict on marital quality of dual career couples in Peshawar, Pakistan. Role conflict i.e. family to work and work to family conflict was taken as independent variable and marital quality was selected as dependent variable. Marital quality was operationalized through four components including satisfaction, communication, togetherness and marital disagreement. Data was gathered through structured questionnaire on three-point Likert type scale from 388 respondents in 6 universities and 3 hospitals in Peshawar city of Pakistan. Results of uni-variate analysis suggest that the study participants were experiencing family to work and work to family conflict. The data further shows that majority of the study participants were having high level of marital quality; nonetheless lower scores were also obtained on all the components of marital quality. Regression analysis suggests that role conflict was significantly and negatively related with marital satisfaction, communication, togetherness and positively related with marital disagreements. Likewise, correlation analysis shows that marital satisfaction, communication and marital togetherness are positively correlated while negatively correlated with marital disagreements. It is concluded from the study that role conflict experienced from either domain reduces marital satisfaction, communication and marital bond while increases marital disagreements between dual career couples.